2009
DOI: 10.1007/s11239-009-0309-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and cost burden of post-thrombotic syndrome

Abstract: Post-thrombotic syndrome (PTS) is a long-term complication of deep-vein thrombosis (DVT), manifesting as swelling, pain, edema, venous ectasia, and skin induration of the affected limb. PTS has been estimated to affect 23–60% of individuals with DVT, frequently occurring within 2 years of the DVT episode. Symptomatic DVT, post-operative asymptomatic DVT, and recurrent DVT are all risk factors for the development of PTS. Treatment of PTS is often ineffective and treatment-related costs represent a healthcare bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(156 citation statements)
references
References 90 publications
3
148
0
5
Order By: Relevance
“…However, contemporary research reported by several authors 25,34 who have employed CDM shows that the recanalization of thrombi in lower extremities with DVT is not a slow process, as was previously believed. Killewich et al have published evidence that lysis of the thrombus and recanalization of venous segments can be observed on CDM in the first week after initial diagnosis 35 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, contemporary research reported by several authors 25,34 who have employed CDM shows that the recanalization of thrombi in lower extremities with DVT is not a slow process, as was previously believed. Killewich et al have published evidence that lysis of the thrombus and recanalization of venous segments can be observed on CDM in the first week after initial diagnosis 35 .…”
Section: Discussionmentioning
confidence: 80%
“…The total additional cost of treating PTS, over 15 years, was approximately US $3,000 in the United States. Additionally, PTS was responsible for 74 to 81% of all DVT treatment costs 25 . A study that analyzed data from patients with diagnoses of PE or DVT estimated that on average health services in the United States spent US$7,000 per patient/year on PTS 25 .…”
Section: Postthrombotic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, post-thrombotic syndrome (PTS), which is a long-term sequela of DVT, aff ects 23 -60 % of patients and results in a high level of morbidity [1]. Several factors contribute to the development of VTE: alterations in blood fl ow, hypercoagulability of blood, and disruption of endothelial function [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 PTS is characterized by swelling, venous eczema, pigmentation, severe edema, venous claudication, chronic pain, and recurrent ulcers. 2 PTS is also associated with a significant health care cost, loss of economic productivity, and a deterioration in quality of life.…”
Section: Introductionmentioning
confidence: 99%